Environmental and economic analysis for the optimal reuse of water in a residential complex. (1st September 2016) - García-Montoya, Mariana; Sengupta, Debalina; Nápoles-Rivera, Fabricio; Ponce-Ortega, José María; El-Halwagi, Mahmoud M.
Abstract: This paper presents an optimization formulation for designing residential water networks involving harvested rainwater and reclaimed wastewater. The design problem is posed as a multi-objective optimization formulation that seeks to balance the objectives of total annualized cost, fresh water consumption, and environmental impact. A life cycle assessment approach is undertaken for estimating the environmental impact. The seasonal dependence of the rainwater is considered in the optimization model. The design approach is applied to a case study for the city of Morelia in Mexico. The results show that significant economic, fresh water consumption, and environmental benefits can be obtained as a result of the proposed approach. Highlights: An optimization model for synthesizing residential water networks is presented. The model considers water reclamation and rainwater harvesting. Life cycle assessment methods are used to evaluate the environmental impact. The proposed method is applied to a case study in a residential complex in Mexico.